ANALISIS PERBANDINGAN PEMODELAN PROPAGASI NILAI LEVEL DAYA TERIMA PADA SISTEM DCS 1800 DI KOTA PONTIANAK - Wawan Tristiyanto . (Faculty of Engineering, Universitas Tanjungpura, 2017)
Digital Communication System 1800 is a derivative standard system of GSM 900. A low transmission power is required for a short network and a propagation condition on 1800 MHz band. Level value of receptivity is an indicator to see a signal quality on the BTS coverage. The purpose of the present research is to analyze receptivity level on DCS 1800 system using Okumura-Hatta, Cost231- Hatta, and Walfisch-Ikegami propagation model. This research took place in the city center by measuring receptivity level which was radiated by using a software namely G-Net Track Lite Signal 4G. Results of the calculation and measurement compared with RSRP standard located in DARATSKIP are presented as follows. Results from Okumura-Hatta propagation model were categorized Very Good -58.04 dBm, - 48.58 dBm, and -66.77 dBm. Cost231-Hatta were categorized Very Good -62.39 dBm, -52.92 dBm, and - 77.11 dBm. Further, Walfisch-Ikegami were categorized Fairly Good -88,44 dBm, Very Good -71.66 dBm, -81,49, G-Net Track Lite Not Good -93 dBm, Very Good -78 dBm, and Good -87 dBm. Comparisons of calculation and measurement at BTS Benua Melayu Darat using Okumura-Hatta propagation model were categorized Very Good -70.68 dBm, -59.28 dBm, and -64.21 dBm. Cost231- Hatta were categorized Very Good -71.79 dBm, -60.38 dBm, -68.57 dBm and G-NetTrack Lite were ranked Very Good -77 dBm and Good -83 dBm, 85 dBm. Further, Walfisch-Ikegami were categorized Very Good -79.8 dBm, Good -83.51 dBm, -86.67 dBm. Comparisons of calculation and measurement at BTS Gajah Mada Mall using Okumura-Hatta propagation model were categorized Very Good -64.97 dBm, -58.59 dBm, and -71.22 dBm. Cost 231-Hatta were categorized Very Good -69.34 dBm, -63.2 dBm, and -76.27 dBm. Finally, Walfisch-Ikegami were categorized Very Good -70.06 dBm, Good -90,65 dBm, - 83,01 dBm, while G-Net Track Lite were Good -84 dBm, and Very Good -68 dBm, -67 dBm. Key words: DCS 1800, RSRP, Okumura-Hatta, Cost231-Hatta,Walfisch-Ikegami.